Upaya Penanggulangan Tindak Pidana Penyalahgunaan Narkotika - Ida Bagus Gede Bawa Mahaputra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2022)
Narcotics abuse has a very bad impact on the continuity of a nation's generation. To anticipate it, it is necessary to cooperate from all components of society, such as families, from school to university levels, and the government must unite in efforts to prevent narcotics in the surrounding environment. The problem formulations of this research are: 1) How is the police investigation process regulated against narcotics abusers? 2) What efforts have been made by law enforcement in preventing narcotics abuse? It is a normative research with the sources of legal material in this study are primary and secondary legal materials, the technique of collecting legal materials uses the method of recording documentation and reading laws and regulations relating to problems and analyzed using qualitative descriptive. From the results of observations and research, the Police are given the authority to conduct investigations and investigate up to the filing of P-21, the Police conduct investigations if there are reports; caught. The implementation of the investigation stems from three things as stated in the Criminal Procedure Code, steps that must be taken by all levels of society in efforts to prevent and control Narcotics in the community, including: 1. Promotive Methods, 2. Preventive Methods, 3. Repressive Methods, 4. Curative Methods, 5 Rehabilitation.